Spatial filtering with rough metal-dielectric layered metamaterials - Stolarek, Marcin; Wróbel, Piotr; Stefaniuk, Tomasz; Wlazło, Mateusz; Pastuszczak, Anna; Kotyński, Rafał (Photonics Letters of Poland, 2013)
Imaging through layered metal-dielectric optical metamaterials may be modeled as linear spatial filtering. We characterize the filtering properties of a thin metal-dielectric-metal multilayer structure evaporated by physical vapor deposition. We present the measurements of transmission spectra, and of surface roughness, as well as the simulation results showing the sensitivity of the structure properties to surface roughness. Surface roughness is found to be the major factor that limits the theoretical filtering properties of the structure. Full Text: PDF References N. Fang, H. Lee, C. Sun, X. Zhang, "Sub–Diffraction-Limited Optical Imaging with a Silver Superlens", Science 308, 534 (2005). CrossRef X. Li, S. He, Y. Jin, "Subwavelength focusing with a multilayered Fabry-Perot structure at optical frequencies", Phys. Rev. B 75, 045103 (2007). CrossRef Z. Jacob, L.V. Alekseyev, E. Narimanov, "Optical Hyperlens: Far-field imaging beyond the diffraction limit", Opt. Expr. 14, 8247 (2006). CrossRef O. Paul, Y. Urzhumov, C. Elsen, D. Smith, M. Rahm, "Construction of invisibility cloaks of arbitrary shape and size using planar layers of metamaterials ", J. Appl. Phys. 111, 123106 (2012). CrossRef C. Guclu, S. Campione, and F. Capolino, "Hyperbolic metamaterial as super absorber for scattered fields generated at its surface", Phys. Rev. B 86, 205130, (2012). CrossRef A. Wood, J. B. Pendry, and D. P. Tsai, "Directed subwavelength imaging using a layered metal-dielectric system", Phys. Rev. B 74, 115116 (2006). CrossRef G. Castaldi, S. Savoia, V. Galdi, A. Alu, N, Engheta, "Analytical study of subwavelength imaging by uniaxial epsilon-near-zero metamaterial slabs", Phys. Rev. B 86, 115123 (2012). CrossRef X. Ni, S. Ishii, M.D. Thoreson, V. M. Shalaev, S. Han, S. Lee, A.V. Kildishev, "Loss-compensated and active hyperbolic metamaterials", Opt. Expr. 19, 25242 (2011). CrossRef M. Scalora, G. D’Aguanno, N. Mattiucci, M.J. Bloemer, D. Ceglia, M. Centini, A. Mandatori, C. Sibilia, N. Akozbek, M.G. Cappeddu, M. Fowler, J. Haus, "Negative refraction and sub-wavelength focusing in the visible range using transparent metallo-dielectric stacks", Opt. Expr. 15, 508 (2007). CrossRef D. de Ceglia, M. Vincenti, M. Cappeddu, M. Centini, N. Akozbek, A. D’Orazio, J. Haus, M.J. Bloemer, M. Scalora, "Tailoring metallodielectric structures for superresolution and superguiding applications in the visible and near-ir ranges", Phys. Rev. A, 77, 033848 (2008). CrossRef C.-H. Liu and N. Behdad, "Tunneling and filtering characteristics of cascaded ?-negative metamaterial layers sandwiched by double-positive layers", J. Appl. Phys. 111, 014906 (2012). CrossRef Yeh, Optical waves in layered media (Wiley 2005). DirectLink N. Mattiucci, D. Aguanno, M. Scalora, M.J. Bloemer, C. Sibilia, "Transmission function properties for multi-layered structures: Application to super-resolution", Opt. Expr. 17, 17517 (2009). CrossRef R. Kotyński, T. Antosiewicz, K. Król, K. Panajotov, "Two-dimensional point spread matrix of layered metal–dielectric imaging elements", J. Opt. Soc. Am. A 28, 111 (2011). CrossRef J. Goodman, Introduction to Fourier Optics (Roberts & Co, 3rd Ed., 2005). L. Novotny, B. Hecht, "Principles of Nano-Optics" (2nd ed. Cambridge Univ. Press 2012). CrossRef A. Caze, R. Pierrat, R. Carminati, "Spatial Coherence in Complex Photonic and Plasmonic Systems", Phys. Rev. Lett. 110, 063903 (2013). CrossRef A.F. Oskooi, D. Roundy, M. Ibanescu, P. Bermel, J. Joannopoulos, S.G. Johnson, "Meep: A flexible free-software package for electromagnetic simulations by the FDTD method", Comput. Phys. Comm. 181, 687 (2010). CrossRef